Analysis of Keloid Response to 5-Fluorouracil Treatment and Long-Term Prevention of Keloid Recurrence. Issue 2 (February 2019) - LaRanger, Ryan; Karimpour-Fard, Anis; Costa, Christopher; Mathes, David; Wright, Woodring E.; Chong, Tae
Abstract : Summary: Keloids are benign fibroproliferative skin tumors that can cause disfigurement and disability. Although they frequently recur after excision or medical management and can affect 6 to 16 percent of African Americans, there is no gold standard therapy. Keloids are challenging to study because there are no animal or in vitro models of this disorder. This makes it very difficult to validate data from treated tissue samples or cells and develop targeted therapies for this disease. In this study, the authors demonstrate that intralesional 5-fluorouracil injection after keloid excision prevents recurrence for 2 years, with no reported adverse events. The authors analyze the expression of treated and untreated biopsy specimens of the same keloids in their native context to capture insights that may be missed by in vitro cell culture models and correct for intrakeloid variability. Random forest analysis of the microarray data dramatically increased the statistical power of the authors' results, permitting hypothesis-free creation of a gene expression profile of 5-fluorouracil–treated keloids. Through this analysis, the authors found a set of genes, including YAP1 and CCL-2, whose expression changes predict 5-fluorouracil therapy status and include genes that have not previously been associated with keloid biology and are of unknown function. The authors further describe keloid heterogeneity for the first time using multidimensional analysis of their microarray results. The methods and tools the authors developed in this research may overcome some of the challenges in studying keloids and developing effective treatments for this disease. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.